2016
DOI: 10.1021/acs.jcim.6b00212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of External Electric Field on Substrate Transport of a Secondary Active Transporter

Abstract: Substrate transport across a membrane accomplished by a secondary active transporter (SAT) is essential to the normal physiological function of living cells. In the present research, a series of all-atom molecular dynamics (MD) simulations under different electric field (EF) strengths was performed to investigate the effect of an external EF on the substrate transport of an SAT. The results show that EF both affects the interaction between substrate and related protein's residues by changing their conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…A force constant of harmonic restraint and a pulling velocity were set to 0.2 kcal mol –1 Å –2 and 5 Å ns –1 , respectively. Through several tests, combined with our previous works, we confirmed that the two parameters are suitable for the present simulation about the unbinding of KAR 1 . While keeping the alpha-carbon (Cα) atoms of three residues (Ser31, Leu77, and Ala102) fixed, external steering force was exerted on the center of mass (COM) of the ligand KAR 1 along the direction determined by the vector from the CG atom (atom name in the force field file) of Leu77 to the O10 atom of the ligand.…”
Section: Computational Detailssupporting
confidence: 78%
See 1 more Smart Citation
“…A force constant of harmonic restraint and a pulling velocity were set to 0.2 kcal mol –1 Å –2 and 5 Å ns –1 , respectively. Through several tests, combined with our previous works, we confirmed that the two parameters are suitable for the present simulation about the unbinding of KAR 1 . While keeping the alpha-carbon (Cα) atoms of three residues (Ser31, Leu77, and Ala102) fixed, external steering force was exerted on the center of mass (COM) of the ligand KAR 1 along the direction determined by the vector from the CG atom (atom name in the force field file) of Leu77 to the O10 atom of the ligand.…”
Section: Computational Detailssupporting
confidence: 78%
“…Until now, however, no simulation work on the KAI2–KAR binding has been reported. In the present research, the detailed binding process of KAR 1 to its receptor protein KAI2, together with the related binding energetics, was investigated by the proper integration of several MD simulation techniques which have been proven to be powerful in addressing similar protein–ligand binding issues. On the basis of steered molecular dynamics (SMD) simulations, the adaptive biasing force (ABF) method was used to obtain the potential of mean force (PMF) of the binding process and reveal the conformational changes of the protein and the ligand. Our simulation results present a dynamic binding view of KAR 1 to KAI2 and will be helpful for the more penetrating understanding of the physiological function of the KAR signal molecule family and their receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cappet et al demonstrated a high level of predictability to calculate binding free energy using homology models with very low identity (∼22%) similar to levels found between hNIS, hSMCT1 and the vSGLT template. Moreover, it should be noted that the ABF method has been applied successfully in evaluations of substrate transport in transmembrane proteins, , whereas the Drude polarizable force field has shown superior accuracy in describing ion–protein interactions . Iodide has the highest polarizability among common monatomic ions and polarizability is particularly important in describing interactions between ions and tryptophan, a residue located in the predicted iodide binding pockets.…”
Section: Discussionmentioning
confidence: 99%